2005
DOI: 10.1002/eat.20132
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-processing deficits in eating disorders

Abstract: The marked impairment in emotion processing found in EDs is independent of affective disorders. Thus, the joint use of TAS and LEAS suggests a global emotion-processing deficit in EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(206 citation statements)
references
References 39 publications
8
190
2
6
Order By: Relevance
“…Within the cognitive impairment in women with ED are distorted beliefs about food, shape and body weight, negative automatic thoughts, dichotomous thinking, representations overarranged about food, weight, and shape, the selective abstraction, overgeneralization, magnification, self-referential ideas and superstitious thinking (García-Camba, 2002). Additionally, it was observed that patients with AN have lower levels of emotional awareness, compared with patients with BN (Bydlowski et al, 2005), although patients with BN have higher impulsivity (Favaro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Within the cognitive impairment in women with ED are distorted beliefs about food, shape and body weight, negative automatic thoughts, dichotomous thinking, representations overarranged about food, weight, and shape, the selective abstraction, overgeneralization, magnification, self-referential ideas and superstitious thinking (García-Camba, 2002). Additionally, it was observed that patients with AN have lower levels of emotional awareness, compared with patients with BN (Bydlowski et al, 2005), although patients with BN have higher impulsivity (Favaro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lane et al (1990) developed the LEAS as an assessment device to rate emotional awareness from the complexity of emotional language that people used (Lumley et al, 2005). Lane and Schwartz (1987) maintain that the degree of structural organization of emotional awareness is reflected in the verbal material used to describe emotional experiences (Bydlowski et al, 2005). As language helps to establish and give structure to concepts it consequently helps to discriminate between distinct emotional states.…”
Section: The Levels Of Emotional Awareness Scale (Leas)mentioning
confidence: 99%
“…Furthermore, as empathy is a cognitive skill that involves applying one's knowledge of one's inner world to the situation of another, there is an increase in empathy as levels of emotional awareness increase. Having a greater capacity for awareness of the emotions of self and other also implies an amplified flexibility in interpersonal interactions and superior adaptational achievement The structural organization of the cognitive process in the levels of emotional awareness model is intimately 11 linked to the increasing structure of knowledge about the internal and external world, the ego, and the ability to take part in interpersonal relationships (Bydlowski, Corcos, Jeammet, Paterniti, Berthoz, Laurier et al, 2005). Therefore, functioning at higher levels of emotional awareness is more desirable than functioning at lower levels.…”
mentioning
confidence: 99%
“…Women diagnosed with eating disorders have lower LEAS scores (both self and others) compared with women without eating disorder diagnoses (Bydlowski et al, 2005). Another study examined a large sample of inpatients diagnosed with psychosomatic disorders and found that the LEAS displayed sensitivity to change in emotional awareness associated with treatment (Subic-Wrana, Bruder, Thomas, Lane, & Kohle, 2005).…”
Section: Emotional Experiencementioning
confidence: 99%